Role of cardiac imaging in patients undergoing catheter ablation of ventricular tachycardia. Issue 10 (October 2021) - Muser, Daniele; Lavalle, Carlo; Guarracini, Fabrizio; Sassone, Biagio; Conte, Edoardo; Magnani, Silvia; Notarstefano, Pasquale; Barbato, Gaetano; Sgarito, Giuseppe; Grandinetti, Giuseppe; Nucifora, Gaetano; Ricci, Renato P.; et al.
Abstract : N/A: Ventricular tachycardia is a major health issue in patients with structural heart disease (SHD). Implantable cardioverter defibrillator (ICD) therapy has significantly reduced the risk of sudden cardiac death (SCD) in such patients, but on the other hand, it has led to frequent ICD shocks as an emerging problem, being associated with poor quality of life, frequent hospitalizations and increased mortality. Myocardial scar plays a central role in the genesis and maintenance of re-entrant arrhythmias, as the coexistence of surviving myocardial fibres within fibrotic tissue leads to the formation of slow conduction pathways and to a dispersion of activation and refractoriness that constitutes the milieu for ventricular tachycardia circuits. Catheter ablation has repeatedly proven to be well tolerated and highly effective in treating VT and in the last two decades has benefited from continuous efforts to determine ventricular tachycardia mechanisms by integration with a wide range of invasive and noninvasive imaging techniques such as intracardiac echocardiography, cardiac magnetic resonance, multidetector computed tomography and nuclear imaging. Cardiovascular imaging has become a fundamental aid in planning and guiding catheter ablation procedures by integrating structural and electrophysiological information, enabling the ventricular tachycardia arrhythmogenic substrate to be characterized and effective ablation targets to be identified with increasing precision, and allowing the development of new ablation strategies with improved outcomes. In this review, we provide an overview of the role of cardiac imaging in patients undergoing catheter ablation of ventricular tachycardia.